Experiences of Social Entrepreneurship Pioneers in Lithuania - Adomaitytė-Subačienė, Ieva; Girkontaitė, Agnė; Petružytė, Donata; Šumskienė, Eglė (Socialinė teorija, empirija, politika ir praktika, 2020)
The phenomenon of social entrepreneurship is sufficiently well-researched abroad since the end of the 20th century. Nevertheless, it is quite a new and under-researched subject in Lithuanian academic discourse. The goal of this article is to explore the experiences of pioneers of social entrepreneurship in Lithuania, the way they create and develop the model of social entrepreneurship. The first half of the article discusses various concepts of social entrepreneurship, its historical development, connections with corporate social responsibility and its purpose in contemporary societies. The second part describes the authentic experiences of being the icebreakers of social business practices in bureaucratic system. Results are based on semi-structured qualitative interviews, conducted in autumn 2018 - spring 2019, with 14 social entrepreneurs in Lithuania. The analysis was done following the approach of grounded theory. The research shows, that social entrepreneurs experience various challenges while cooperating with governmental institutions or municipalities while searching for suitable funding models and experiencing ignorance from society in general. Nevertheless, they still engage in these activities with the help and support of an emerging community of active like-minded social entrepreneurs, whose support is essential for the existence and development of social entrepreneurship in Lithuania.